Make your place : affordable, sustainable nesting skills - Briggs, Raleigh (Portland, Or. : Microcosm Publishing, 2018)
"A hand-written and illustrated guide to herbal and nontoxic first aid, gardening, and housekeeping"--
Safety protocols -- Health and first aid -- Non-toxic cleaning & body care -- Gardening.
Includes bibliographical references.
Keywords: Home economics; Sustainable living